2006
DOI: 10.1021/om050805l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Ethylene Oligomerization and Polymerization of [2,6-Bis(2-benzimidazolyl)pyridyl]chromium Chlorides

Abstract: A series of [2,6-bis(2-benzimidazolyl)pyridyl]chromium chlorides have been synthesized and characterized by elemental analysis and IR spectroscopy, along with X-ray diffraction analysis for the structures of C1 and C7. When methylaluminoxane (MAO) was employed as the cocatalyst, the chromium complexes showed high activity for ethylene oligomerization and polymerization. Oligomers were produced with high selectivity for α-olefins, and polyethylenes were generated with extremely broad molecular weight distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 58 publications
10
94
0
1
Order By: Relevance
“…The use of higher temperatures and increased amounts of MAO afforded 65 polyethylene of broader molecular weight distribution, ie catalysis by multi-active species. 19,[38][39][40][41][42] For the 2-(1-aryliminoethylidene)quinoline complexes 33 -42 (Scheme 7), 36 activation with MMAO led to good activity for ethylene dimerization; the iron(II) pre-catalysts exhibited higher activities and a better selectivity for α-butene. 36 The activity trends (iron) 35 > 37 > 36 > 34 > 33 (entries 1, 5-8, Table 7) and (cobalt) 40 > 42 > 41 > 39 > 38 (entries 9, 13-16, Table 7) were observed.…”
Section: Bi-dentate Iron and Cobalt Pre-catalystsmentioning
confidence: 99%
“…The use of higher temperatures and increased amounts of MAO afforded 65 polyethylene of broader molecular weight distribution, ie catalysis by multi-active species. 19,[38][39][40][41][42] For the 2-(1-aryliminoethylidene)quinoline complexes 33 -42 (Scheme 7), 36 activation with MMAO led to good activity for ethylene dimerization; the iron(II) pre-catalysts exhibited higher activities and a better selectivity for α-butene. 36 The activity trends (iron) 35 > 37 > 36 > 34 > 33 (entries 1, 5-8, Table 7) and (cobalt) 40 > 42 > 41 > 39 > 38 (entries 9, 13-16, Table 7) were observed.…”
Section: Bi-dentate Iron and Cobalt Pre-catalystsmentioning
confidence: 99%
“…When the methyl group is introduced in the meta-position to the imino-nitrogen atom (39, 46, 53) it leads to an increase of the activity due to both electronic and steric effects. On the other hand, when the methyl group is introduced in the para position (40, 47, 54) with respect to the imino nitrogen atom, the activities drop because the electron density on the nitrogen atom increases and consequently the nucleophilicity of the central metal atom increases which weakens the interaction between the metal atom and the p-electrons of the ethylene monomer and hence this decreases the rate of ethylene insertion in the chain-growth steps 27,45 .…”
Section: Fig 14: Dsc Curve For the Polyethylene Produced With The Camentioning
confidence: 99%
“…In polyolefin chemistry, an increasing interest has been focused on the exploration and development of homogeneous transition metal catalysts, as a result of an increasing demand for polyethylene [25][26][27][28][29][30] . The vanadium complexes of bis(benzimidazole)amine tridentate ligands [N, N, N], were reported as active ethylene polymerization catalysts after activation with simple alkylaluminum compounds 31 2,6-Bis(2-benzimidazolyl)pyridine zirconium dichloride / MAO polymerizes methylacrylate 32 Recently, [33][34][35][36][37][38][39] we reported the ethylene polymerization activity of benzimidazole, benzothiazole, benzoxazole and 2-(benzimidazolyl) pyridine titanium zirconium and vanadium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium complexes bearing NNN ligands exhibited high catalytic activities in ethylene oligomerization and polymerization [15,21,22]. It is reported that chromium complexes ligated by NNN species such as bis(imino)pyridine, (2-pyridylmethyl)amines, β-diketimate and pyrrolide-imine ligands can polymerize or oligomerize ethylene with great activity [21,[23][24][25].…”
Section: Nnn Ligandsmentioning
confidence: 99%
“…It is reported that chromium complexes ligated by NNN species such as bis(imino)pyridine, (2-pyridylmethyl)amines, β-diketimate and pyrrolide-imine ligands can polymerize or oligomerize ethylene with great activity [21,[23][24][25].…”
Section: Nnn Ligandsmentioning
confidence: 99%